تفعيل مفهوم التسامح فلسفياً (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2014)
عانت المجتمعات البشرية من تفاقم مظاهر التعصب والعنف واللاتسامح, مما أحدث خللاً في الأسس والمبادئ والقيم التي تحكم العلاقة بالآخر لدرجة إقصائه فكرياً وسياسياً ودينياً وإنسانيا .... فغياب التسامح أو تغيبه يؤدي إلى سيادة عقلية التحريم والتجريم. بالمقابل اكتسب مفهوم التسامح معانٍ عدة, وتجسد بصور متنوعة عبر اختلاف أشكال الوعي الإنساني, فلم يعد التسامح مقتصراً على الجانب الطائفي والديني بل امتد ليشمل الجانب السياسي الحقوقي الاجتماعي, الإثني ....... لهذه المسائل مجتمعة أنبرى الفلاسفة لإثارة الكثير من القضايا والمسائل المتعلقة بالتسامح, فكانت الفلسفة من أكثر الميادين المعرفية التي عملت على ترسيخه في العقل البشري. وبما أن الحاجة تدعو اليوم –كما في فترات عديدة من التاريخ البشري– إلى بعث الحياة في القيم الإنسانية السامية وإخصابها ونشرها، فقد يكون من المناسب التدقيق في مفهوم التسامح بربطه بالفلسفة، باعتبار أن الفلسفة هي المركز التي تمتحن فيها المفاهيم والمجال الحيوي لإغنائها ومنحها القوة، قوة التأثير في الفكر والسلوك. فالتسامح المأمول راهناً ليس فضيلة فحسب بل هو ضرورة وجودية اجتماعية وثقافية وسياسية، وذلك من أجل تحصين واقعنا أمام كل مخاطر الدوغمائية والتعصب الأعمى الذي يمكن أن يحيط بنا ويستهدف وجودنا وتطلعاتنا. Human societies suffered from worsening manifestations of intolerance and violence and intolerance, Creating an imbalance in the foundations and principles and values ​​that govern the relationship of the other so remove him intellectually and politically, religiously and humanly ….. The absence of tolerance lead to rule mentality of prohibition and criminalization. Conversely acquired the concept of tolerance many different meanings, and reflected a variety of images across different forms of human consciousness, Tolerance is no longer confined to the sectarian and religious side, but extended to the political, legal social side , Ethnic  ....... ,These issues combined kick philosophers to raise a number of issues and issues relating to tolerance. Philosophy was one of the most fields of knowledge which has worked to entrench in the human mind. .As the need for today - as in many periods of human history - To breathe life into the lofty human values ​​and fertilized and dissemination, It may be appropriate to scrutinize the concept in terms of the philosophy of tolerance, Considering that philosophy is that test center where concepts and vital area to enrich and give them strength, impact strength in thought and behavior. Tolerance is hoped wagered not only a virtue but a necessity and existential social, cultural and political need. And in order to fortify the reality in front of all the risks of dogmatism and bigotry that can take us and targeting our existence and our gains and our aspirations.